TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP BENTUK KERJASAMA BISNIS PERIKLANAN ANTARA PUBLISHER DAN GOOGLE ADSENSE - Muhammad, Mahlil Nur; Hidayat, Fatah; Sadi' Is, Muhammad (Muamalah, 2021)
The research background discusses Google adsense, which is an advertising business collaboration program that is very popular in the world online today. Anyonecan become an advertiser for Google with easy conditions, but the fact is that the adsdisplayed by Google are very general, from the sale of food, services and even Googlealso sometimes displays ads selling liquor, gambling to pornography which in Islam isprohibited. From this phenomenon, researchers are interested in examining GoogleAdsense with the formulation of the problems in this study, namely: 1) What is the formof advertising business cooperation between publishers and Google Adsense. 2) How isthe review of Islamic economic law on the form of advertising business collaborationbetween publishers and Google Adsense. The method used in this research is the research library or library research,which is collecting various secondary data that discusses the form of advertisingbusiness collaboration between publishers and Google Adsense both from the media,journals and literature. The results of data processing were analyzed descriptivelyqualitatively. Based on the results of the study it can be concluded that: 1) the form ofadvertising business collaboration between publishers and Google Adsense. Is a form ofcooperation to advertise a product or service owned by the advertiser. With 68% profitsharing for publishers and 32% for Google. So if a publisher is cheating, the adsenseaccount publisher's will be banned. 2) in the review of sharia economic law, this form ofcooperation is included in the form of syirkah abdan and the law is valid if theadvertisements displayed by Google do not contain haram elements. Because in thecooperation itself, it has been fulfilled, such as consent to Kabul, aqidain and itsobjects. Keywords:Business Online, Google Adsense, Syirkah Abdan